Digital Leadership and Digital Transformation: The Role of Change Readiness, Person-Organization Fit, and Person-Job Fit - Khan, Muhammad Tasnim; Asghar, Nabila; Rehman, Hafeez ur; Abbas, Iqra (Pakistan Journal of Humanities and Social Sciences, 2025)
Technological artificial intelligence and digitalization are rapidly transforming business environments across the globe, compelling organizations to reassess their strategies, structures, and leadership approaches. In this context, the present study examines the impact of two critical leadership styles, digital leadership (DL) and digital transformational leadership (DTL), on the process of digital transformation (DT) within organizations, specifically through the mediating role of change readiness (CR). Furthermore, this study explores the moderating effects of person-organization fit (POF) and person-job fit (PJF) on these relationships. To analyze these relationships, researchers targeted the information and communication technology (ICT) industry in Pakistan. The study targeted 150 ICT firms, and survey-based questionnaires will be implemented with 350 employees. Researchers employed SmartPLSv4.1.1.2 to analyze first-hand survey-based data. Grounded in transformational leadership theory (TLT), the findings are expected to reveal that DL and DTL significantly contribute to building a robust organizational culture that is conducive to digital transformation. Moreover, CR plays a critical mediating role, highlighting the psychological and behavioral preparedness of employees to embrace digital initiatives. Moreover, POF and PJF play a moderating role and boost the impact of CR on DT. Finally, this research emphasized theoretical and practical implications and ensured that these efforts are crucial to sustain innovation, competitiveness, and long-term success in the digital era.